Cortical atrophy and amyloid and tau deposition in Down syndrome: A longitudinal study. Issue 1 (1st April 2022) - Padilla, Concepcion; Montal, Victor; Walpert, Madeleine J.; Hong, Young T.; Fryer, Tim D.; Coles, Jonathan P.; Aigbirhio, Franklin I.; Hartley, Sigan L.; Cohen, Ann D.; Tudorascu, Dana L; Christian, Bradley T.; Handen, Benjamin L.; et al.
Abstract: Introduction : The Down syndrome population has a high prevalence for dementia, often showing their first clinical symptoms in their 40s. Methods : In a longitudinal cohort, we investigate whether amyloid deposition at time point 1 (TP1) could predict cortical thickness change at time point 2 (TP2). The association between tau burden and cortical thickness was also examined at time point 3 (TP3). Results : Between TP1 and TP2 there was pronounced cortical thinning in temporo‐parietal cortices and cortical thickening in the frontal cortex. Baseline amyloid burden was strongly associated to cortical thinning progression, especially in the temporo‐parietal regions. At TP3, tau deposition negatively correlated with cortical atrophy in regions where tau usually accumulates at later Braak stages. Discussion : A higher amount of amyloid accumulation triggers a cascade of changes of disease‐causing processes that eventually lead to dementia. As expected, we found that regions where tau usually accumulates were those also displaying high levels of cortical atrophy.